(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article discusses the rearrangement of the synthesized series of derivatives of 2’-hydroxychalcones, the structures of new compounds in the PMR spectra are proved, and the thionization reactions are studied. As a result of the research, anti-tuberculosis activity was found.